Activity-centered design : an ecological approach to designing smart tools and usable systems. - Gay, Geri, ....-; Hembrooke, Helene, ....- (Cambridge : MIT, 2004)
Series Foreword Preface: Mediating Interactions Acknowledgments Introduction: Making the Case for Context-Based Design 1 Activity Theory and Context-Based Design 2 Understanding Perspectives: Social Construction of Technology 3 Creating a Sense of Place: Designing for Online Learning Conversations 4 Blurring Boundaries: A study of Ubiquitous Computing 5 Designing for Context-Aware Computing 6 Configural Analysis of Spaces and Places References Index